Consensus statement on cardiovascular risk stratification and aggressive management of chronic coronary syndromes - Balaji, P.; Jadhav, Uday; Roy, Devanu Ghosh; Zachariah, Geevar; Shah, M. K. (International Journal of Advances in Medicine, 2023)
Cardiovascular diseases (CVDs) are responsible for 17.5 million deaths globally, and India is more susceptible to coronary artery disease (CAD) than its western counterparts because of certain challenges such as suboptimal management, increased healthcare costs, and physicians undermining the extent of limitation in angina patients. All of these could be resolved by employing strategies starting with accurate diagnosis to timely implementation of aggressive management techniques to contain morbidity and mortality. Pan India, experts from the field of cardiology came together in order to discuss risk stratification and aggressive management of chronic coronary syndromes (CCS). The expert consensus laid down a path of recommendations considering the prevailing healthcare service infrastructure, local evidence-based studies and key international guidelines. With the wide diversity in terms of geographical distribution in India and the risk factors presented across various divisions of the population, risk stratification is necessary for prompt identification and subsequent management of CCS. In this consensus, various risk stratification techniques such as risk stratification based on ventricular function, electrocardiogram (ECG), stress echocardiography (ECHO), the Duke treadmill score (DTS), and myocardial perfusion imaging (MPI) were discussed. After risk stratification, the consensus focused on aggressive management of CVDs with therapeutic optimization for various types of patient profiles such as revascularization for stable angina and angina with comorbidities (diabetes and renal failure), apart from emphasis on various medications and their roles in ameliorating disease symptoms.